2000
DOI: 10.1021/ja9942890
|View full text |Cite
|
Sign up to set email alerts
|

Ru(II)-Catalyzed Cycloadditions of 1,6-Heptadiynes with Alkenes:  New Synthetic Potential of Ruthenacyclopentatrienes as Biscarbenoids in Tandem Cyclopropanation of Bicycloalkenes and Heteroatom-Assisted Cyclocotrimerization of 1,6-Heptadiynes with Heterocyclic Alkenes

Abstract: The ruthenium(II)-catalyzed tandem cycloaddition of 1,6-heptadiynes with bicyclic alkenes, such as bicyclo[3.2.1]heptenones and norbornene derivatives, furnishes the 1:2 adducts between the diynes and two molecules of the bicycloalkenes together with common [2 + 2 + 2] cyclocotrimerization products. The structure of a representative tandem 1:2 adduct between dimethyl dipropargylmalonate and 2,4-dimethylbicyclo[3.2.1]-oct-6-en-3-one was unequivocally determined by X-ray analysis and was concluded to involve an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(59 citation statements)
references
References 81 publications
(71 reference statements)
2
55
1
1
Order By: Relevance
“…The formation of intermediates D and E corresponds to alkene and enyne metathesis key steps. The novelty of this catalytic reaction is related to the last step: a promoted reductive elimination from E to give 2, rather than the classical formation of the enyne metathesis product the alkenylcycloalkene F. On interaction of ruthenium-carbene moiety with an alkene, this reductive elimination step is favoured [20] probably because of the steric hindrance of the C 5 Me 5 -Ru group, as we showed that [Cp*RuCl(cod)] also catalyzed the same reaction but afforded derivatives of 2 in lower yield.…”
mentioning
confidence: 99%
“…The formation of intermediates D and E corresponds to alkene and enyne metathesis key steps. The novelty of this catalytic reaction is related to the last step: a promoted reductive elimination from E to give 2, rather than the classical formation of the enyne metathesis product the alkenylcycloalkene F. On interaction of ruthenium-carbene moiety with an alkene, this reductive elimination step is favoured [20] probably because of the steric hindrance of the C 5 Me 5 -Ru group, as we showed that [Cp*RuCl(cod)] also catalyzed the same reaction but afforded derivatives of 2 in lower yield.…”
mentioning
confidence: 99%
“…Ruthenium-catalyzed cycloaddition of dicyanides: To A C H T U N G T R E N N U N G achieve a selective and efficient pyridine formation, we employed a neutral ruthenium(ii) complex, [Cp*RuClA C H T U N G T R E N N U N G (cod)] (1), having both an electron-donating planar ligand (Cp* = pentamethylcyclopentadienyl) and a readily leaving supporting ligand (cod = 1,5-cyclooctadiene), as this proved to be an efficient precatalyst for the cycloaddition of the a,w-diynes with alkenes, [11] alkynes, [12] isocyanates and isothiocyanates, [13] or tricarbonyl compounds. [14] The reaction of dimethyl dipropargylmalonate (2 a) and two equivalents of acetonitrile in the presence of 1 mol % 1 in 1,2-dichloroethane (DCE) at room temperature (around 25 8C), however, gave only a mixture of dimers and trimers of 2 a. Diyne 2 a was recovered quantitatively if the reaction was carried out with acetonitrile as a solvent.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to 3 b, dicyanides connecting a more rigid tether gave better results. For example, ortho-, meta-, and para-dicyanobenzenes 3 d-3 f were allowed to react with 2 a, delivering the corresponding pyridines 4 ad-4 af in 43-61 % yield (runs [10][11][12]. In these cases, the product yields appeared to depend on the distance between the two cyano groups.…”
Section: Resultsmentioning
confidence: 99%
“…[56] When dimethyl dipropargylmalonate 67 is reacted with an excess of norbornene and chloro(η 5 -indenyl)ruthenium(1,5-cycloocatdiene) 70 , polycyclic 68 is formed as the primary reaction product, with minor amounts of diene 69 . However, when indenyl complex 70 is exchanged for its cyclopentadienyl analogue 71 , more of the diene is formed in proportion to 68 .…”
Section: Iron and Rutheniummentioning
confidence: 99%